Fungal colonization before or after lung transplantation has no negative impact on survival or the development of chronic lung allograft dysfunction - Embla Bodén; Fanny Sveréus; Anna Niroomand; Hamid Akbarshahi; Richard Ingemansson; Hillevi Larsson; Sandra Lindstedt; Franziska Olm (JHLT Open)
Introduction: Long-term survival following lung transplantation (LTx) faces impediments due to chronic lung allograft dysfunction (CLAD), while infections hinder short-term survival. Fungal colonization and invasive fungal infections (IFI) are common within the first year after LTx. There is ongoing debate regarding the impact of such events on CLAD development and mortality. This study aims to investigate this matter further. Methods: A total of 134 LTx recipients transplanted between 2011 and 2020 were included. The median follow-up time was 3.9 years. Fungal colonization and IFI were defined according to international consensus guidelines and were noted if present within the first 12 months after LTx. Results: Postoperative fungal colonization was found in 101 patients, and 14 patients had an IFI within twelve months of transplantation. Nineteen patients were neither colonized nor infected. Out of the 115 patients with colonization or IFI, 61 patients had growth of a yeast such as Candida species (spp.). Fifty-six patients were colonized prior to LTx. Being colonized with fungus before or within the first 12 months post-LTx did not significantly affect survival or CLAD development. Conclusions: The results of the current study indicate that fungal colonization either pre-transplantation or within the first 12 months after does not correlate with increased risks of mortality or CLAD development. These findings show that while fungal colonization is a common occurrence in LTx recipients, it does not predispose the patients of the cohort to adverse outcomes.